2011
DOI: 10.1021/am200805x
|View full text |Cite
|
Sign up to set email alerts
|

Nanoforest Nb2O5 Photoanodes for Dye-Sensitized Solar Cells by Pulsed Laser Deposition

Abstract: Vertically aligned bundles of Nb(2)O(5) nanocrystals were fabricated by pulsed laser deposition (PLD) and tested as a photoanode material in dye-sensitized solar cells (DSSC). They were characterized using scanning and transmission electron microscopies, optical absorption spectroscopy (UV-vis), and incident-photon-to-current efficiency (IPCE) experiments. The background gas composition and the thickness of the films were varied to determine the influence of those parameters in the photoanode behavior. An opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 26 publications
5
75
0
Order By: Relevance
“…The capability of KBNNO to absorb 3 to 6 times more solar energy than the current ferroelectric materials suggests a route to viable ferroelectric semiconductor-based cells for solar energy conversion and other applications. Although several other oxides or mixed oxides, such as ZnO, SnO 2 , Nb 2 O 5 , and Zn 2 SnO 4 have also been reported as photoanodes for DSSCs, [191][192][193][194][195][196][197][198] these materials always exhibit lower photovoltaic performance compared with DSSCs with TiO 2 . Similar results have also been reported by Zhou et al, 182 and it was observed that KBNNO with compositions of x = 0.1-0.3 have a narrow E bg of below 1.5 eV, which is much smaller than the 3.2 eV BG of the parent KNbO 3 (KNO) due to the increasing Ni 3d electronic states within the gap of KNO.…”
Section: Other Perovskite-based Light Absorbersmentioning
confidence: 99%
“…The capability of KBNNO to absorb 3 to 6 times more solar energy than the current ferroelectric materials suggests a route to viable ferroelectric semiconductor-based cells for solar energy conversion and other applications. Although several other oxides or mixed oxides, such as ZnO, SnO 2 , Nb 2 O 5 , and Zn 2 SnO 4 have also been reported as photoanodes for DSSCs, [191][192][193][194][195][196][197][198] these materials always exhibit lower photovoltaic performance compared with DSSCs with TiO 2 . Similar results have also been reported by Zhou et al, 182 and it was observed that KBNNO with compositions of x = 0.1-0.3 have a narrow E bg of below 1.5 eV, which is much smaller than the 3.2 eV BG of the parent KNbO 3 (KNO) due to the increasing Ni 3d electronic states within the gap of KNO.…”
Section: Other Perovskite-based Light Absorbersmentioning
confidence: 99%
“…11a). 44 As can be seen, the APCE of the cells varies in the same trend with IPCE in the wavelength range with 1/N719 > 2/N719 > N719. Meanwhile, the absorption of N719 is compensated by the complexes, which leads to an enhanced light harvesting efficiency.…”
Section: Photovoltaic Properties Of Dsscsmentioning
confidence: 67%
“…Over several decades, nanostructured metal oxides were synthesized by various vacuum-based synthesis methods such as evaporator, 13,14 sputtering, 15 chemical vapor deposition (CVD), [16][17][18][19] pulsed laser deposition (PLD) 20 and other techniques. Recently, a hydrothermal reaction was practiced to make metal oxide nanostructure z E-mail: maxko@snu.ac.kr as a core material for the hierarchical nanostructure.…”
Section: Synthesis Of Metal Oxide Nanostructure By Hydrothermal Procementioning
confidence: 99%